2022
DOI: 10.1002/mgg3.1960
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of pregnant women in the Kingdom of Saudi Arabia toward Noninvasive prenatal testing: A single center study

Abstract: Background Noninvasive prenatal testing (NIPT) is a screening tool for chromosomal aneuploidies. Prior knowledge of NIPT is an inherent factor in the decision‐making process. We assessed the knowledge and attitude of pregnant women related to prenatal testing with a particular focus on NIPT. Methods A prospective cross‐sectional study, using a culturally validated questionnaire, was conducted with 342 pregnant women of whom 74.9% consented for prenatal screening. Mean age and gestational weeks ± standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…In the present study, awareness about NIPT among pregnant women was notably low (7%). A study conducted in Saudi Arabia reported awareness levels of 43.9% among pregnant women, with a significant association between education level and knowledge of NIPT [ 19 ]. A Swedish study reported that 59.8% of expecting mothers were aware of NIPT [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, awareness about NIPT among pregnant women was notably low (7%). A study conducted in Saudi Arabia reported awareness levels of 43.9% among pregnant women, with a significant association between education level and knowledge of NIPT [ 19 ]. A Swedish study reported that 59.8% of expecting mothers were aware of NIPT [ 20 ].…”
Section: Discussionmentioning
confidence: 99%